The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1088/2752-5295/ad0e13
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on global potato yields: a review

Toyin Adekanmbi,
Xiuquan Wang,
Sana Basheer
et al.

Abstract: Potatoes as a food crop contribute to zero hunger: Sustainable Development Goal 2. Over the years, the global potato supply has increased by more than double consumption. Changing climatic conditions are a significant determinant of crop growth and development due to the impacts of meteorological conditions, such as temperature, precipitation, and solar radiation, on yields, placing nations under the threat of food insecurity. Potatoes are prone to climatic variables such as heat, precipitation, atmospheric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 139 publications
0
1
0
Order By: Relevance
“…It was found that intercropping lettuce, cucumber, and tomato is preferable to practicing monocultures from an economic standpoint [105]. Studies have indicated that the impact of vegetable cultivation on global warming is notable, primarily attributed to substantial greenhouse gas emissions arising from energy consumption, irrigation, agricultural practices, and fertilizer usage, with specific emphasis on greenhouse environments [108,109]. Conservation management practices can improve the productivity of crops and lower the carbon footprint by 31% [110].…”
Section: Cropping System Managementmentioning
confidence: 99%
“…It was found that intercropping lettuce, cucumber, and tomato is preferable to practicing monocultures from an economic standpoint [105]. Studies have indicated that the impact of vegetable cultivation on global warming is notable, primarily attributed to substantial greenhouse gas emissions arising from energy consumption, irrigation, agricultural practices, and fertilizer usage, with specific emphasis on greenhouse environments [108,109]. Conservation management practices can improve the productivity of crops and lower the carbon footprint by 31% [110].…”
Section: Cropping System Managementmentioning
confidence: 99%